Column Adsorption Studies for the Removal of Cr(VI) Ions by Ethylamine Modified Chitosan Carbonized Rice Husk Composite Beads with Modelling and Optimization - S. Sugashini; K. M. Meera Sheriffa Begum (Journal of Chemistry)
The objective of this present study is the optimization of process parameters in adsorption of Cr(VI) ions by ethylamine modified chitosan carbonized rice husk composite beads (EAM-CCRCBs) using response surface methodology (RSM) and continuous adsorption studies of Cr(VI) ions by ethylamine modified chitosan carbonized rice husk composite beads (EAM-CCRCBs). The effect of process variables such as initial metal ion concentration, adsorbent dosage and pH were optimized using RSM in order to ensure high adsorption capacity at low adsorbent dosage and high initial metal ion concentration of Cr(VI) in batch process. The optimum condition suggested by the model for the process variable such as adsorbent dosage, pH and initial metal ion concentration was 0.14 g, 300 mg/L and pH2 with maximum removal of 99.8% and adsorption capacity of 52.7 mg/g respectively. Continuous adsorption studies were conducted under optimized initial metal ion concentration and pH for the removal of Cr(VI) ions using EAM-CCRCBs. The breakthrough curve analysis was determined using the experimental data obtained from the continuous adsorption. Continuous adsorption modelling such as bed depth service model and Thomson model were established by fitting it with experimental data.